A Sustainable Solar Photovoltaic Energy System Interfaced with Grid-Tied Voltage Source Converter for Power Quality Improvement. Issue 2 (20th January 2017) - Singh, Bhim; Jain, Chinmay; Goel, Sagar; Gogia, Rahul; Subramaniam, Umashankar
Abstract: This paper deals with the design, modeling, and implementation of a photovoltaic (PV) array interfaced with a DC–DC boost converter feeding three-phase grid-tied voltage source converter. The system uses an Instantaneous Reactive Power Theory-based control algorithm and is operated in unity power factor mode. This three-phase shunt-connected solar PV energy conversion system is also used for load currents harmonics elimination, power factor correction, reactive power compensation, and grid currents balancing in a three-phase distribution system. A Perturb and Observe-based maximum power point tracking algorithm is used to generate maximum power from the PV array. This system is designed and modeled, and its performance is verified through simulation in MATLAB/Simulink. A prototype of the proposed renewable energy system is developed in the laboratory using a digital signal processor to validate its design and control.